Features of Ukraine’s image in the media space of the French Republic in the pre-war period (1991 – 2013) - Dovhan, Anna (Young Scholars Grinchenko – Seton International Journal, 2025)
The article presents a study of the peculiarities of forming Ukraine’s image in France after the declaration of independence in 1991. It describes the key areas influencing the perception of Ukraine in the French media space, including political relations, economic challenges, sports events, and culture. The main characteristics of Ukraine’s representation in the French media are analysed, and the dynamics of their changes are illustrated in the context of internal and foreign political developments.